Where Winners Live - Galindo, Linda; O'Malley, Sharon; Porter, Dave (Ascent Audio, 2020)
Personal accountability is the secret weapon of every successful sales professional. It is the secret weapon of Where Winners Live co-author Dave Porter, who became the owner and CEO of Baystate Financial Services at age 35 and grew it into a $100 million-a-year business over the next 15 years. It is the secret weapon of Where Winners Live co-author Linda Galindo, who transformed herself from the self-proclaimed Queen of Victims into an entrepreneur, business coach, consultant and speaker whose typical audience numbers 500 or more. Like all highly accountable professionals, these authors live Where Winners Live, an achievement they say is available to everyone. Written in a no-excuses tone and filled with personal stories and practical exercises, their book offers readers the non-negotiable, high-performance behaviors of the sales trade and tried-and-true best practices for success, and: Exposes the key difference between top-earning sales professionals and those who struggle to make their numbers every quarter. Outlines the three critical characteristics of personal accountability: responsibility, self-empowerment, and ownership of results after the fact. Explores personal accountability from the perspective of both leaders and rank-and-file sales professionals. Shows readers the most effective way to hold themselves and others accountable.